Analyzing the Opportunities and Challenges of Establishing International Branch Campuses (IBCs) in Indonesia - Anisa Nurhasanah (NeoRespublica : Jurnal Ilmu Pemerintahan, 2026)
Globalization has accelerated the internationalization of higher education through various forms of transnational education, including the establishment of International Branch Campuses (IBCs). In recent years, Indonesia has increasingly embraced the presence of IBCs as part of its broader strategy to enhance the quality of higher education and strengthen the global competitiveness of its human capital. This study aimed to analyze the opportunities and challenges associated with the establishment of IBCs within Indonesia's higher education ecosystem. Employing a qualitative research approach, the study utilized document analysis of government regulations, reports published by national and international institutions, news articles, and scholarly literature on transnational education and International Branch Campuses. Data validity was ensured through source triangulation by systematically comparing information from government documents, international organizations, and academic publications. The findings revealed that IBCs offer several strategic advantages, including expanding access to internationally recognized education at a more affordable cost, enhancing the quality of domestic higher education institutions through competitive pressure and the transfer of best practices, and supporting human capital development, particularly in science, technology, engineering, and mathematics (STEM) disciplines. Nevertheless, the expansion of IBCs also poses significant challenges, including widening educational inequality due to high tuition costs, the geographical concentration of campuses on Java Island that may exacerbate regional disparities, the growing dominance of foreign institutions in knowledge production, and intensified competition faced by local universities. Therefore, the successful implementation of Indonesia's IBC policy requires a balanced regulatory framework that simultaneously promotes openness to international branch campuses while strengthening the institutional capacity and long-term competitiveness of domestic higher education institutions.